PENGARUH POSISI PEMOTONGAN BAHAN STEK DAN PEMBERIAN EKSTRAK BAWANG MERAH TERHADAP PERTUMBUHAN STEK TANAMAN STEVIA (Stevia rebaudiana B.) - Khaerunnisa, Mahdelia Alyaa; Karno, Karno; Kristanto, Budi Adi (BUANA SAINS, 2023)
This research aimed to determine the effect of cutting position and the concentration of onion extract as a natural hormone on stevia stem cutting propagation. This study used a Factorial Completely randomized design in which the first factor was Apical Cutting (P1), Middle cutting (P2), and Bassal Cutting (P3), and the second factor was control (R0), shallot extract concentration 25% (R1), shallot extract concentration 50%(R2), shallot extract concentration 75% (R3), shallot extract concentration 100% (R4) and Rootone F 25 ppm (R5). The position of cutting has significantly resulted in Times of bud growth, number of roots, number of leaves, and plant height. The concentration of shallot extract has significant results in times of bud growth, number of roots, length of root, number of leaves, plant height, weight of plant, and weight of dry plant. The best performance was apical cuttings and shallot extract concentration of 100%.